Effect of cognitive-behavioral therapy-based physical play intervention on empathic ability of children with intellectual disabilities - Guanting Duan; Yisiqi Wang; HuiSheng Hou; Tian Li (Scientific Reports)
Abstract Purpose The purpose of this study was to investigate the potential of cognitive-behavioral therapy-based sports game intervention in enhancing empathy abilities among children with intellectual developmental disorder. Methods Thirty-one children aged 7–8, diagnosed with intellectual developmental disorder and attending mainstream schools, were enlisted for this study. They were randomly allocated to either the experimental group (n = 17) or the control group (n = 19). Both groups participated in regular physical activities of similar frequency and consistency throughout the study duration. Additionally, the experimental group underwent an 18-week cognitive-behavioral therapy-based sports game intervention. The Griffith Empathy Measure (GEM) questionnaire was administered to comprehensively evaluate the impact of the intervention program on the participants’empathy abilities. Results No statistically significant discrepancies were observed in the total scores and factor scores of the GEM pre-test between the experimental and control groups (GEM pre-test: p = 0.974 > 0.05). However, following the intervention, the experimental group exhibited notably higher total scores and factor scores in the GEM post-test compared to their pre-test scores, and these scores were significantly higher than those of the control group post-test scores. Conclusion Cognitive-behavioral therapy-based sports game intervention can effectively promote the development of empathy abilities in children with intellectual developmental disorder.